Implementing Effective & Efficient Security Service Management in Mining Company - Santoso, Joko; Mulyono, Nur Budi (Law Development Journal, 2023)
Security in a business, especially in the mining industry, is a paramount necessity for the company's sustainability. The assurance of security is also a determining factor for a company's productivity in carrying out its activities. Therefore, the management of an effective and efficient physical security system is required to support the company's operations in producing and gaining profits. The ultimate goal of security management is the creation of a conducive situation that can minimize threats, disturbances, obstacles, or challenges that disrupt a company's operations. In the day-to-day operations of an organization that manages a physical security system, it must undoubtedly have an effective and efficient organizational structure. Its existence should serve as a guideline for security personnel themselves as well as for users or stakeholders in a company, thus ensuring effectiveness and efficiency as per expectations. In this research, the researcher will conduct a study on the effective management of the security division's organizational structure during the transition from permanent employees to outsourcing or contract employees in the mining industry sector. In the ongoing transition process, the researcher has identified gaps in various stages, including planning, communication, implementation, and development. Therefore, there is a need for improvisation on what has been done. By conducting qualitative research, security managers in mining companies will receive guidance and guidelines based on the research when undergoing the transition from permanent security personnel to outsourcing, while still adhering to the security rules and standards of mining companies in Indonesia and globally. The recommendations from this research emphasize the need for a Needs Analysis and Risk Assessment by security managers when undergoing the transition process. This involves a comprehensive identification of the core tasks and functions of a security officer in a mining company, thus gaining a clear understanding of the quantity, qualifications, and types of skills required for contract or outsourcing employees in the mining company.